Macroeconomic Variables and Jakarta Islamic Index (JII) in Indonesia: an Approach of Error Correction Model - Dian Wahyudi; Abdul Qoyum (Sunan Kalijaga: Islamic Economics Journal, 2022)
The purpose of this study is to examine the impact of macroeconomic variables on the Jakarta Islamic Index (JII) over the period 2012-2021. Macroeconomic variables include inflation, the exchange rate, the bi-rate, global oil prices, and the price of gold. In this study, the Error Correction Model (ECM) was used to examine the short- and long-term impact of macroeconomic variables on the di Jakarta Islamic Index (JII). According to the findings, the Indonesian sharia exchange rate and Bi-Rate had an impact on the sharia stock index in the short run. In contrast, interest rates, global oil prices, and global gold prices have a long-term impact on the sharia stock index. Variable inflation has no effect on either.